HUBUNGAN PERILAKU SISWA SEKOLAH DASAR DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN DOLOK BATU NANGGAR KABUPATEN SIMALUNGUN TAHUN 2023 - Bahtera David Purba; Pitto Malau; Ripando Jhon Sembiring; Usaha Tarigan (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
Dengue hemorrhagic fever is an infectious disease that can cause extraordinary events (KLB). Dengue Hemorrhagic Fever spreads in Southeast Asia. Western Pacific & Caribbean. Indonesia is an endemic region that has spread to all corners of the country. According to the North Sumatra Provincial Health Ministry, the number of dengue hemorrhagic fever (DHF) sufferers in the region between January and September 2022 was 5,270 cases. According to the Simalungun District Health Office, in December 2022 there were 999 cases of dengue fever and 13 deaths in Simalungun. The results of the initial study of student behavior are still not enough to eradicate mosquito nests (PSN). This type of research is a quantitative study with an analytic observation study design using cross-sectional methods. This research was conducted in the elementary school area 091690 Serbelawan. The population in this study were elementary school students in Dolok Batu Nanggar Elementary School. In this study the analysis used the chi-square or chi-square formula (x2). . The results showed that there was a relationship between the behavior of throwing garbage and the incidence of DHF at the level of p = 0.045, namely <α = 0.05. There is a relationship between the behavior of draining the bathtub and the incidence of DHF at the level of p = 0.020, namely <α = 0.05. There is no relationship between the use of anti-mosquito lotion and the incidence of DHF at the level of p=0.684, namely <α = 0.05. It is suggested to the head of the Puskesmas to develop health education about the dangers of dengue fever mosquitoes.